PENDAMPINGAN IBU HAMIL DALAM UPAYA PENINGKATAN STATUS GIZI - Ismaulidia Nurvembrianti; Intan Purnamasari; Astri Sundari (Politeknik 'Aisyiyah Pontianak, 2021)
Background: Pregnancy is a decisive period for the quality of growth and development of children who are born, during pregnancy greatly determines the condition of the fetus in the womb. Nutritional needs during pregnancy have an important role in the condition of the mother and fetus. Pregnant women who have poor nutrition will experience Chronic Energy Deficiency (KEK) and cause risks and complications of pregnancy. The risk of pregnancy that occurs in pregnant women with KEK can cause fatal health problems such as congenital defects and will trigger preterm birth and IUGR. The purpose of this service is to increase knowledge about pregnant women's nutrition. The method uses discussion and demonstration. The participants of this activity were pregnant women in Tengguli Village, Sajat District, Sambas Regency. The results showed that there was an improving knowledge for pregnant women and could make menus related to balanced nutrition during pregnancy.